Rerpresentasi Nilai Antikorupsi, Toleransi, dan Partisipasi Program Mata Najwa di Narasi - A Munanjar; Mirza Ronda; Rhatika Diana (Cakrawala - Jurnal Humaniora, 2022)
The title of this research is Representation of Anti-Corruption Values, Tolerance, and Participation in the Mata Najwa Program in Narasi. Narasi in collaboration with Trans7 broadcasts the Mata Najwa program every Wednesday at 20.00 WIB. This program consistently maintains the quality of broadcast content by bringing values of anti-corruption, tolerance, and participation. These values are not only the foundation in preparing the material or content in each episode, but also want to build critical thinking in society (especially the younger generation) and make them move for a better Indonesia. This research is descriptive qualitative which aims to understand the representation of the value of the Mata Najwa program in Narasi, and the message of the Mata Najwa program. The unit of analysis in this study is the selection of three episodes that represent the anti-corruption value (Serba Pungli episode), tolerance value (Once Again Problem Tolerance episode), and participation value (Warga Bantu Warga episode). The unit of analysis was dissected using Roland Barthes' semiotic theory which looked at the denotations, connotations, and myths of the Mata Najwa talkshow program instrument, which was then interpreted by Stuart Hall's representation theory. The results of the study found that the representation of the value of anti-corruption represents the value of preventing corruption and the opportunity for corruption to develop by increasing individual awareness not to commit corruption and how to save money and state assets. Tolerance represents the value of respecting every difference, being open to other people's ways of thinking, accepting, and respecting the values that other people have. And participation represents the value of the involvement of individuals or groups to take roles and take responsibility for development, environmental empowerment, political, religious issues, or decision-making, policies, and government services. The representation of the value of the Mata Najwa program as a medium creates a culture of anti-corruption, tolerance and audience participation, as well as being a vehicle for narrative media to transfer ideology in order to build and expand social relations.